Mitchell-Riley Syndrome: A Novel Mutation in RFX6 Gene. (3rd December 2015) - Zegre Amorim, Marta; Houghton, Jayne A. L.; Carmo, Sara; Salva, Inês; Pita, Ana; Pereira-da-Silva, Luis
Abstract : A novel RFX6 homozygous missense mutation was identified in an infant with Mitchell-Riley syndrome. The most common features of Mitchell-Riley syndrome were present, including severe neonatal diabetes associated with annular pancreas, intestinal malrotation, gallbladder agenesis, cholestatic disease, chronic diarrhea, and severe intrauterine growth restriction. Perijejunal tissue similar to pancreatic tissue was found in the submucosa, a finding that has not been previously reported in this syndrome. This case associating RFX6 mutation with structural and functional pancreatic abnormalities reinforces the RFX6 gene role in pancreas development and β -cell function, adding information to the existent mutation databases.